Organisational Change Framework for Lean Manufacturing Implementation - Norani Nordin; Baba Md Deros (International Journal of Supply Chain Management, 2017)
Lean manufacturing system is a proven approach for success in manufacturing companies worldwide. However, several companies have failed in their attempt to implement this system. The transition to lean manufacturing system requires a radical change which involves a total reshaping of purpose, system, and work culture. This paper develops a framework that may assist manufacturing companies to implement lean manufacturing system. This study has employed explanatory mixed method approach, which begins with survey distribution and is followed by in-depth interviews at Malaysian automotive companies to further refine the general picture attained from the survey. Both quantitative and qualitative results show that the key factors to managing a smooth transition to lean manufacturing are: change readiness, leadership and management, the change-agent system, team development and empowerment, communication, and the review system. The results also serve as the basis for developing organizational change that aids the framework implementation for lean manufacturing system. This framework has strong theoretical significance because of its explicit focus on the relationship between lean manufacturing and the management of its implementation. This framework may also provide practitioners with a better understanding of the transition process to lean manufacturing, which will minimize potential resistance and conflicts and thus improve the systems chances of success. Failure to recognize the organizational changes towards lean manufacturing system may hinder the systems long-term benefits to organization.